Site Suitability Analysis for Solid Waste Landfill Site Location Using Geographic Information Systems and Remote Sensing: A Case Study of Banket Town Board, Zimbabwe - Zulu, Sam; Jerie, Steven (LAR Centre Press, 2022)
The aim of this study was to map the optimal sites that were environmentally suitable for locating a dumpsite in the Zimbabwean townof Banket as well as investigating the suitability of the dumpsite being currently used by the Banket Town Board. Geographic Information Systems and remote sensing constituted the main quantitative techniques used in data collection. Digitizing, bufferingand overlaying were used to map suitable sites for locating a dumpsite in Banket. Environmental parameters were extracted from Google Earth by way of digitizing, buffered using Quantum GIS 2.8 and then overlaid using Quantum GIS 2.8 to produce the suitability map. In support of the quantitative techniques, qualitative techniques that included interviews, questionnaires, observations and literature were used to compliment the quantitative methods. Results of the research presented a suitability map which showed the possible suitable sites for establishing a dumpsite in Banket as well as the most considered suitable site in the eastern part of the town. In mapping the suitable sites according to a number of buffered parameters (Central Business District, Railway line, Road, and Rivers) the current dumpsite was found to lie within the parameters designated as unsuitable. It was recommended that Banket should consider closing its current dumpsite for a better location from the possible suitable sites establishedby the study especially the site on the eastern part of the town which is suitable in terms of all buffered parameters as well as other confounding variables that include economy, accessibility and elevation as well as slope.